2017
DOI: 10.3390/rs9080767
|View full text |Cite
|
Sign up to set email alerts
|

Gauging the Severity of the 2012 Midwestern U.S. Drought for Agriculture

Abstract: Different drought indices often provide different diagnoses of drought severity, making it difficult to determine the best way to evaluate these different drought monitoring results. Additionally, the ability of a newly proposed drought index, the Process-based Accumulated Drought Index (PADI) has not yet been tested in United States. In this study, we quantified the severity of 2012 drought which affected the agricultural output for much of the Midwestern US. We used several popular drought indices, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…This result is consistent with those obtained in previous studies [14]. For example, Zhang [18,52] indicated that the agricultural drought index increases with meteorological drought.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with those obtained in previous studies [14]. For example, Zhang [18,52] indicated that the agricultural drought index increases with meteorological drought.…”
Section: Discussionsupporting
confidence: 93%
“…RSDIs are used to quantitatively evaluate the effects of drought and directly determine the accuracy of drought monitoring; therefore, it is particularly important to study their capability under different spatio-temporal patterns. However, few studies have combined RSDIs with the meteorological drought index to assess whether the remotely sensed index is suitable for drought monitoring, and the research on the capability of RSDIs under different spatio-temporal patterns is insufficient [28,29]. Moreover, most of the methods to evaluate capability are based on a single statistical indicator (e.g., average deviation and root-mean-square error).…”
Section: Introductionmentioning
confidence: 99%
“…First, other drought indices such as the Palmer drought severity index (Palmer, 1965) and the standardized precipitation index (McKee et al., 1993) can also be used. Second, the risk indicators can be more diverse and comprehensive, and different indicators may result in inconsistent results (Yao et al., 2018; Zhang et al., 2017). For instance, other socioeconomic factors that influence exposure and vulnerability, such as the age/sex structure, the industrial structure, and the distribution of reservoirs should also be considered when the data are available.…”
Section: Discussionmentioning
confidence: 99%